Assessing strategic social partnerships between professional sports teams and NPOs in Australian football. Issue 3 (4th June 2019) - Rayne, Daniel; McDonald, Heath; Leckie, Civilai
Abstract : Purpose: The purpose of this paper is to assess corporate social responsibility (CSR) implemented via social partnerships between professional sports teams and not-for-profit organizations according to current theoretical perspectives. Limited resources and outcomes often mean there is a gap between theory and practice, the implications of which are not well understood. Design/methodology/approach: Five partnerships in Australian football were analyzed via case study methodology which incorporated interviews, analysis of websites, social media and annual reports. Findings: Despite being used as a CSR tool, findings showed most organizations enter these arrangements to achieve instrumental outcomes. Further, such partnerships mostly operate at a basic stage often described as philanthropic. One partnership was seen as more advanced consisting of a workplace plan to enhance diversity. Practical implications: It is advocated that managers adopt a more integrated partnership model consisting of formalized objectives, activity implementation, evaluation mechanisms, frequent interaction, top-level leadership involvement and promotion to sufficiently achieve CSR goals. Originality/value: Addressing calls from past research into an examination of the variation of CSR in sports, this research is one of the first to compare multiple case studies to assess the strategic implementation of social partnerships in a professional sporting context. Accordingly, the study demonstrates how such partnerships can be evaluated against a prominent theoretical model, the Collaboration Continuum, enabling more robust social partnership strategies.